Evaluasi Desain Furniture PAUD di Siwalankerto, Surabaya - Valeria Grisca Tjahjono (Intra, 2017)
This evaluation was conducted to determine the furniture design of Early Childhood Education School in Siwalankerto Surabaya based on curriculum applied in Indonesia. Study furniture is a resource that is directly related to the activity as well as children’s learning activities that took place in the classroom. In the design of furniture, there are several factors that need to be considered because it can affect the performance of its users. This research is conducted by using quantitative qualitative research approach which is expected to know all information from 5 schools of Early Childhood Education which have been traced one by one to get a proven. The results showed that some of the furniture that used by teachers and students in inside and outside the class in each school has a problem that is not much different related to the shape, material, color, finishing, security, and ergonomic so it can be suggested some solution in the use of furniture which is good for PAUD schools.